Investigation of Tolstoi Mountain iron deposits, Kasaan Peninsula, Prince of Wales Island, southeastern Alaska - Erickson, Aner W.; United States. Bureau of Mines. ([Washington, D.C.] : U.S. Dept. of the Interior, Bureau of Mines, 1948)
"December 1948." Mode of access: Internet.